Impacto da idade do policial rodoviário federal no perfil e evolução de afastamentos para licença de saúde: um estudo de coorte retrospectiva - Freitas, Flavio Castagna de (2019)
Introduction: If on the one hand population aging is to be celebrated, on the other hand such factor becomes a challenge these days. Demographic changes resulting from the mentioned population aging impact several fields of society, such as health, labor and social security, areas which have been on the spotlight in Brazil in present days, due to the ongoing changes to the retirement rules. One of the external factors that influences the pace and quality of aging is the exposition to stressing events, including those related to labor activities. Federal Highway Patrol Officers (initials in Portuguese as: APRF) is among the professions with this characteristic, since the stress is inherent to their labor activities, strengthening the risk of chronic-non-transmissible diseases. This professional context has negative consequences for the worker and the institution, such as the decrease of productivity, quality of work, a raise of absenteeism, temporary disability, early retirement and lower life expectancy. Federal Highway Police Department, through organizational aspects such as age, can be contributing to this, considering that the institution does not establish an age limit to the starting or the permanence in the career, differently from other departments of police. However, there are not enough studies on the theme which subsidize management improvement to this profession. Hence, this study aimed to identify if variables such as the worker present age, age of starting and length of work in the institution have any connection with cases of sick leaves, what could explain the labor conditions of these workers. Objectives: Analyze the impact of male and female APRF within the aimed profile and the evolution of absences from work to sick leaves within the period of 2014 to 2018 and its connection with other intervenient factors. Methods: An analysis of a previous cohort was led through personal data of 8,399 working Federal Highway Patrol Officers from 01/01/2014 to 31/12/2018. For this study, Age, gender, duration of sick leave and length of work were used as descriptive variables, while “sick leave” and “starting age” were used as study variables. The unfold of the concession of sick leaves were analyzed with linear regression. The study population was categorized in individuals who demanded sick leave and those who did not demand it, comparing the main differences between the groups. The statistic comparisons were performed by nonparametric analyzes: Comparison of independent samples by Wilcoxon-Mann-Whitney test, test of medians by Kruskall-Wallis analysis, Category Analysis by Chi-square test or Fisher’s exact test. To identify possible intervenient variables among sick leaves and age of the worker a Backward Wald multivariable logistic regression was performed, which enabled the calculation of relative risk of variables for sick leaves. All the statistic tests were considered significant when the values were p<0,05. Results: The average age of men was 41,21 ± 7,49 years old (average = 40,7), while the average of women was of 39,76 ± 8,32 years old (average = 38). The demographic and functional profiles of the Highway Patrol Officers showed differences including higher incidence of male individuals, which aged ≥ 40 years old, than female individuals. A relatively high number of individuals of both genders were away from work due to sick leaves.However, the progression remained stable at 45,7 ± 9,3% the annual average of workers away from work. Age impacted significantly the frequency and the time of days away from work. This result was also similar between genders. The connection between age and sick leaves showed no relation to the age of starting the career or the region of the country where the worker was located. The relative risk of officers leaving work at least once a year is 2,28 and 1,55 times higher for men and women respectively than when compared to age ranges of younger officers. Conclusion: Age impacted significantly the frequency and the duration of the sick leaves. Such results reassure the suggestion that the length of service of the officer is limited, probably by aspects inherent to the duty. These results could assist the organization of personnel management within the Federal Highway Patrol Police Department, mostly in the sense of mitigating the impact of the triad work-age-health on the Federal Highway Patrol Officer and optimize the efficiency of the services offered to the society.